Non Performing Loan Moderates Influence Credit Provided By LPD Profitability In LPD Gianyar Sub-District - EKAJAYANTI, L.G.P Sri; MANUABA, I. B. Putra; SANJAYA, I Ketut Puja Wirya (PT Keberlanjutan Strategis Indonesia, 2023)
The Village Credit Institution (LPD) is a financial business entity owned by a traditional village and carries out business activities within the traditional village environment. LPD is one of the assets and sources of income for traditional villages, so it requires good management by management and supervisory bodies. In general, the LPD aims to improve the standard of living of villagers and to preserve the existence of traditional villages in the Province of Bali. The Village Credit Institution (LPD) is a financial institution owned by Desa Pakraman which has special characteristics. This specificity is mainly related to the obligations of the LPD towards Desa Pakraman which are physical/scale as well as non-physical/niskala. Regarding the LPD in the Gianyar sub-district, there are 40 LPD spread across the Gianyar sub-district. The purpose of this study was to determine the effect of credit extended by LPD on profitability with non-performing loans as a moderating variable. This type of research is an empirical study of LPDs throughout the Gianyar District. The sampling technique used was purposive sampling, namely sampling based on consideration, so the sample in this study was 165 samples obtained from 33 LPD populations throughout the Gianyar District with 5 years of observation, namely from 2017-2021 and data collection was carried out with documentation. The data analysis technique used is Partial Last Square (PLS) where the independent variables are credit extended by LPD, the dependent variable is profitability and the moderating variable is non-performing loans.